PROINFLAMMATORY EFFECTS OF LAUNAEA TARAXACIFOLIA AQUEOUS LEAVES EXTRACT IN BENZENE INDUCED HAEMATOTOXICITY IN ALBINO MALE WISTAR RATS - Obazelu, Progress Arhenrhen; E. Wasa, Favour (Nigerian Journal of Pharmaceutical and Applied Science Research, 2024)
Background: Haematotoxicity induced by benzene exposure has been associated with altered gene expressions of proinflammatory cytokines, such as interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-?). Launaea taraxacifolia, a plant known for its traditional medicinal uses, has emerged as a subject of interest due to its reported anti-inflammatory properties. Therefore, the aim of this study was to determine the proinflammatory effects of aqueous leaf extracts of Launaea taraxacifolia on benzene-induced haematotoxicity in albino Wistar rats. Methods: A total of sixty (60) adult male albino Wistar rats were divided into six (6) groups, namely groups A, B, C, D, E, and F, representing control, benzene group, cyclophosphamide group, benzene + 100mg/kg Launaea taraxacifolia, benzene + 200mg/kg Launaea taraxacifolia, and benzene + 400mg/kg Launaea taraxacifolia, respectively. mRNA expressions of IL-6 and TNF-? were determined using polymerase chain reaction (PCR). The data obtained was analysed by the Statistical Package for Social Science (SPSS) software. Results: mRNA expression of IL-6 in group B was significantly higher when compared to group A (p<0.05).The mRNA expression of IL-6 was significantly higher in groups E and F when compared to group A (p<0.05). There was a significant increase in the mRNA expression of TNF-? in group B when compared to group A (p<0.05). Conclusion: This study concludes that benzene exposure induces an increase in the mRNA expression of IL-6 and TNF-?. Co-administration of benzene and varying Launaea taraxacifolia concentrations subsequently reduced TNF-?, while a further increase was noted in IL-6 expression after administration of 200mg/kg with benzene.